Giant Dermoid Cyst Causing Dysphagia and Dyspnea. Issue 3 (May 2016) - Derin, Serhan; Koseoglu, Sabri; Sahan, Leyla; Dere, Yelda; Sahan, Murat
Abstract : Abstract: Dermoid cysts are benign lesions seen in young adults. The second most common localization is the floor of the mouth. They are usually asymptomatic over years but can be symptomatic due to secondary changes or the size. Herein, we report a case of 19-year-old woman who applied to emergency service with dyspnea, dysphagia and enlarging of a mass in the submental region. The patient cannot be entubated because of the mass pushing the tongue base backward closing the laryngeal view. Elective tracheostomy was performed for providing airflow during the operation. After the operation a cystic mass fulfilled with keratin lined by keratinized stratified squamous epithelium in addition to the dermal appendages such as sweat glands and follicular structures were seen histopathologically and the case was diagnosed as dermoid cyst of the submental region. In such patients with quick enlarging of mass causing airway obstructions, the tracheostomy can be the preferable method because of the difficulties in entubation.